Practical Recommendations for Robot-Assisted Treadmill Therapy (Lokomat) in Children with Cerebral Palsy: Indications, Goal Setting, and Clinical Implementation within the WHO-ICF Framework - Tabea Aurich (-Schuler); Warken, Birgit; Graser, Judith V.; Ulrich, Thilo; Borggraefe, Ingo; Heinen, Florian; Meyer-Heim, Andreas; van Hedel, Hubertus J. A.; Schroeder, A. Sebastian (Neuropediatrics, 2015)
Active participation and the highest level of independence during daily living are primary goals in neurorehabilitation. Therefore, standing and walking are key factors in many rehabilitation programs. Despite inconclusive evidence considering the best application and efficacy of robotic tools in the field of pediatric neurorehabilitation, robotic technologies have been implemented to complement conventional therapies in recent years. A group of experienced therapists and physicians joined in an “expert panel.” They compared their clinical application protocols, discussed recurring open questions, and developed experience-based recommendations for robot-assisted treadmill therapy (exemplified by the Lokomat, Hocoma, Volketswil, Switzerland) with a focus on children with cerebral palsy. Specific indications and therapeutic goals were defined considering the severity of motor impairments and the International Classification of Functioning, Disability and Health framework (ICF). After five meetings, consensus was found and recommendations for the implementation of robot-assisted treadmill therapy including postsurgery rehabilitation were proposed. This article aims to provide a comprehensive overview on therapeutical applications in a fast developing field of medicine, where scientific evidence is still scarce. These recommendations can help physicians and therapists to plan the child's individual therapy protocol of robot-assisted treadmill therapy.
Keywords: child; cerebral palsy; rehabilitation; robotics; International Classification of Functioning, Disability and Health